Method for stabilizing recycled aggregate in municipal road base by using lime and fly ash

By determining the particle grading and material mix ratio of recycled aggregates in construction waste, combined with lime fly ash, two ash stable recycled aggregates that meet the requirements of municipal roads were prepared, which solved the problems of low dosage and unstable performance, and achieved the Efficient use of construction waste to meet the construction needs of municipal roads.

CN119121724APending Publication Date: 2024-12-13QINGDAO GREEN SAIL RECYCLED BUILDING MATERIALS +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411243425.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

In the prior art, when preparing lime fly ash stable material for road base lime, fly ash, the amount of recycled aggregates in construction waste is low, the performance is unstable, and it is difficult to meet the construction requirements of municipal roads.

Method used

By determining the grading and material mixing ratio of recycled aggregates, the recycled aggregates of construction waste are screened into coarse aggregates and fine aggregates, combining lime and fly ash to ensure that the mixed two ash is stable in the recycled aggregates meet the optimal water content The requirements for rate, maximum dry density and compressive strength are adopted, and the laying method of multi-layer road structure layer is carried out, and strict inspection and construction processes are carried out to improve the amount and performance of the material.

Benefits of technology

It has achieved 100% of the recycled aggregate of construction waste instead of natural aggregate, which has improved the utilization rate of construction waste, protected the ecological environment, excellent material performance, complied with relevant technical specifications, and improved the construction feasibility of municipal roads.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119121724A_ABST
    Figure CN119121724A_ABST
Patent Text Reader

Abstract

The invention discloses a method for stabilizing recycled aggregate by using lime and fly ash in a municipal road base. The method comprises the following steps: determining the grain composition of recycled coarse aggregate and recycled fine aggregate and the mix proportion of lime, fly ash and synthesized recycled graded aggregate; designing a plurality of road structure layers according to the grade requirement and the traffic volume requirement of the municipal road; and performing paving, rolling and maintenance construction procedures according to the designed paving layer structure of the lime-fly ash stable recycled aggregate. The method comprises the following steps: firstly, determining the grain composition of the recycled aggregate, then providing a paving structure layer of a general municipal road, and finally providing a general process and method for paving the lime-fly ash stabilized recycled aggregate, and compared with the existing application method of the inorganic binder stabilized recycled aggregate, the method provided by the invention has the advantages that the technical performance of the material is ensured; the mixing amount of the construction waste recycled aggregate is greatly increased, 100% replacement of natural aggregate is realized, the utilization rate of the construction waste is greatly increased, a novel paving application method is provided for municipal roads, and the feasibility of practical application is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of road engineering, and in particular to a method for applying lime fly ash to stabilize recycled aggregate in a municipal road base. Background Art

[0002] With the acceleration of urbanization, the output of construction waste has increased dramatically, bringing great pressure to the environment. Traditional methods of construction waste disposal, such as landfill or transportation, not only occupy a large amount of land resources, but also may cause environmental pollution and waste of resources. Therefore, the resource utilization of construction waste has become an important issue at present. By utilizing recycled construction waste, the exploitation of natural resources can be significantly reduced, environmental pollution can be reduced, and sustainable development can be achieved. The use of recycled aggregates from construction waste to prepare lime fly ash stabilized materials for road bases has gradually been recognized by engineering.

[0003] However, due to the complex composition and unstable performance of recycled aggregates from construction waste, the dosage of recycled aggregates in the current preparation methods is relatively low. Summary of the invention

[0004] The invention provides a method for stabilizing recycled aggregate by applying lime fly ash in a municipal road base to solve the above problems.

[0005] In order to achieve the above object, the technical solution of the present invention is:

[0006] A method for stabilizing recycled aggregate by applying lime fly ash to a municipal road base comprises the following steps:

[0007] S1: Determine the particle size distribution and material mix ratio of recycled aggregate:

[0008] The crushed construction waste recycled aggregate is screened into recycled coarse aggregate and recycled fine aggregate according to the particle size specifications, and the gradation ratio of the recycled coarse aggregate and the recycled fine aggregate is determined according to the crushing index, water absorption rate and gradation curve of the construction waste recycled aggregate to ensure that the crushing index, water absorption rate and gradation curve of the synthetic recycled graded aggregate formed by mixing the recycled coarse aggregate and the recycled fine aggregate meet the corresponding design requirements;

[0009] Determine the mix ratio of the three based on the optimal moisture content, maximum dry density, and 7d unconfined compressive strength of the fly ash stabilized recycled aggregate formed by mixing lime, fly ash, and synthetic recycled graded aggregate, to ensure that the optimal moisture content, maximum dry density, 7d unconfined compressive strength, mass loss rate in the frost resistance test, and residual compressive strength ratio meet the corresponding design requirements;

[0010] S2: Design road structure layer:

[0011] According to the grade requirements and traffic volume requirements of municipal roads, the road structure layer paved with fly ash stabilized recycled aggregate mixed according to the recycled aggregate particle grading and material mix ratio determined in S1 is set as a multi-layer road structure layer paved from bottom to top;

[0012] S3: Paving of fly ash stabilized recycled aggregate:

[0013] Conduct screening tests, physical property tests, and chemical property tests on lime, fly ash, and synthetic recycled graded aggregates to ensure that each test result meets the corresponding standards;

[0014] Carry out compaction test, ash dosage test, 7d unconfined compressive strength test, frost resistance test indoor test, core drilling test, rebound deflection test, compaction test on-site performance test for fly ash stabilized recycled aggregate to ensure that each test result meets the corresponding design requirements;

[0015] The paving, rolling and curing construction procedures are carried out according to the paving structure of fly ash stabilized recycled aggregate designed in S2.

[0016] Furthermore, in S1, the mass ratio of the lime, fly ash and synthetic recycled graded aggregate is 8:17:75.

[0017] Furthermore, in S1, the recycled coarse aggregate includes two particle sizes of 5 to 10 mm and 10 to 25 mm; the recycled fine aggregate includes one particle size of 0 to 5 mm;

[0018] The grading ratio of the 0-5 mm recycled fine aggregate, the 5-10 mm recycled coarse aggregate and the 10-25 mm recycled coarse aggregate is 24:26:50.

[0019] Furthermore, in S2, the multi-layer road structure layer includes an upper base layer, a lower base layer and a low base layer arranged in sequence from top to bottom, wherein the thickness of the upper base layer is 18 cm, the thickness of the lower base layer is 18 cm, and the thickness of the bottom base layer is 16 cm.

[0020] Furthermore, in S1, the crushing index of the recycled aggregate of construction waste is that the crushing rate of recycled coarse aggregate is less than 22%, and the crushing rate of recycled fine aggregate is less than 30%;

[0021] The water absorption rate of recycled aggregate from construction waste is less than 9.5%;

[0022] The specification requirements for the gradation curve of mixed recycled aggregates from construction waste are: the upper limit of the gradation curve of 19.0mm recycled coarse aggregate is 86.0%, and the lower limit is 68.0%; the upper limit of the gradation curve of 9.5mm recycled coarse aggregate is 58.0%, and the lower limit is 38.0%; the upper limit of the gradation curve of 4.75mm recycled fine aggregate is 32.0%, and the lower limit is 22.0%; the upper limit of the gradation curve of 2.36mm recycled fine aggregate is 28.0%, and the lower limit is 16.0%; the upper limit of the gradation curve of 0.60mm recycled fine aggregate is 15.0%, and the lower limit is 8.0%; the upper limit of the gradation curve of 0.075mm recycled fine aggregate is 3.0%, and the lower limit is 1.0%.

[0023] Furthermore, in S2, the grade of municipal roads is level 2 and below, and the traffic volume requirement is equivalent to less than 7,500 cars per day and night.

[0024] Furthermore, in S1, the optimum moisture content is 11.1%, the maximum dry density is 2.015 g / cm3, and the 7d unconfined compressive strength is 2.80 MPa.

[0025] Furthermore, in S3, the test results of the screening test, physical property test, and chemical property test of lime, fly ash, and recycled aggregate shall meet the requirements of CJJ1-2019 Code for Construction and Quality Acceptance of Urban Road Engineering and JTG / TF20-2015 Technical Specifications for Highway Pavement Base Construction;

[0026] The measurement results of the compaction test, ash dosage test, 7d unconfined compressive strength test, frost resistance test for indoor tests of fly ash stabilized recycled aggregate, and the core test, rebound deflection test, and compaction test for on-site performance testing must meet the following standards: the optimal moisture content of the compaction test is not less than 11.1% and the maximum dry density is not less than 2.015g / cm3; the ash dosage range of the upper base, lower base, and bottom base in the ash dosage test is 33% to 34%; the 7d unconfined compressive strength is not less than 2.8MPa; the mass loss rate of the frost resistance test is less than 5%, and the residual compressive strength ratio is greater than 70%; the core sample of the core test is smooth and straight, the average thickness of the bottom base of the core sample is greater than 155mm, the average thickness of the lower base is greater than 175mm, and the average thickness of the upper base is greater than 175mm, and the 30d coring strength meets 7 to 9MPa; the representative value of 9d deflection in the rebound deflection test is greater than 20 (0.01mm); and the compaction test meets greater than 95%.

[0027] Furthermore, in S3, the paving method is: paving by a paver with a paving speed of 1.0 to 1.5 m / min.

[0028] Furthermore, before the fly ash stabilized recycled aggregate is spread, a process of transporting the fly ash stabilized recycled aggregate to the construction site is provided, and measures are taken to prevent moisture loss during transportation.

[0029] The beneficial effects of the present invention are:

[0030] The present invention discloses a method for applying lime fly ash stabilized recycled aggregate in the base of a municipal road. First, the particle gradation of the recycled aggregate is determined. Then, based on the characteristics of the lime fly ash stabilized recycled aggregate, a paving structure layer of a general municipal road is proposed. Finally, based on the road construction specifications, a general process and method for paving the fly ash stabilized recycled aggregate are proposed. Compared with the existing application method of inorganic binder stabilized recycled aggregate, the method greatly increases the dosage of construction waste recycled aggregate while ensuring the technical performance of the material, achieves 100% replacement of natural aggregate, greatly improves the utilization rate of construction waste, protects the ecological environment, and alleviates the shortage of natural materials. Moreover, the prepared material meets the requirements of relevant technical specifications, has excellent performance, and has the technical performance for engineering use. At the same time, the present invention proposes a new paving application method for municipal roads, which greatly improves the feasibility of practical application. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0032] Figure 1 A flow chart of a method for applying lime fly ash to stabilize recycled aggregate in a municipal road base provided by an embodiment of the present invention;

[0033] Figure 2 The gradation curve results of the screening test for recycled aggregates of three particle sizes;

[0034] Figure 3 This is the gradation curve result diagram after the proportion of three specifications of particle size is determined;

[0035] Figure 4 The figure is the result of the unconfined compressive strength test of fly ash stabilized recycled aggregate;

[0036] Figure 5 It is a schematic diagram of the road structure layer structure (including asphalt surface layer);

[0037] Figure 6 This is the result of the unconfined compressive strength test of fly ash stabilized recycled aggregate in the test section;

[0038] Figure 7 This is the result of the frost resistance test of fly ash stabilized recycled aggregate in the test section;

[0039] Figure 8 The first coring and core sample diagram of the test section (a is the schematic diagram of the first coring, and b is the core sample diagram of the bottom base, lower base and upper base taken out of the first coring);

[0040] Fig. 9 The second coring and core sample diagram of the test section (a is the schematic diagram of the second coring, and b is the core sample diagram of the bottom base, lower base and upper base taken out of the second coring);

[0041] Fig.10 The thickness test results of the core samples taken for the first coring and the second coring in the test section are shown in the figure;

[0042] Fig.11 The unconfined compressive strength test results of the core samples taken from the first coring and the second coring of the test section are shown in the figure;

[0043] Fig.12 Figure 1 is a graph showing the compaction test results of the core samples taken for the first coring and the second coring in the test section (a is a graph showing the dry density test results of the core samples taken for the two corings, and b is a graph showing the compaction test results of the core samples taken for the two corings). DETAILED DESCRIPTION

[0044] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0045] like Figure 1 The method for stabilizing recycled aggregate by applying lime fly ash to a municipal road base provided by this embodiment includes the following steps:

[0046] S1: Determine the particle size distribution and material mix ratio of recycled aggregate:

[0047] The crushed construction waste recycled aggregate is sieved into recycled coarse aggregate and recycled fine aggregate according to the particle size specifications. The recycled coarse aggregate includes two particle sizes of 5-10mm and 10-25mm; the recycled fine aggregate includes one particle size of 0-5mm. The three particle sizes of recycled aggregate are sieved separately, and the results are as follows: Figure 2 As shown; Figure 2In the process, the gradation composition of recycled aggregate is poor, and the particle size is relatively concentrated, especially about 90% of the aggregates of 5-10mm are concentrated around 5mm. In order to prevent the particle size distribution from restricting the bulk density and compressive performance and affecting the structural characteristics of the road base, three types of aggregates need to be mixed;

[0048] The grading ratio of recycled coarse aggregate and recycled fine aggregate is determined according to the crushing index, water absorption rate and grading curve of recycled aggregate from construction waste, ensuring that the crushing index, water absorption rate and grading curve of the synthetic recycled graded aggregate formed by mixing the recycled coarse aggregate and the recycled fine aggregate meet the corresponding design requirements. The crushing index is that the crushing rate of recycled coarse aggregate is less than 22%, the crushing rate of recycled fine aggregate is less than 30%; the water absorption rate is less than 9.5%; the specification requirements for the grading curve of the synthetic recycled graded aggregate formed by mixing the recycled aggregate from construction waste are: the grading upper limit of 19.0mm recycled coarse aggregate is 86.0%, and the lower limit is 68.0%; the grading upper limit of 9.5mm recycled coarse aggregate is 58.0%, and the lower limit is 38.0%; the grading upper limit of 4.75mm recycled fine aggregate is 68.0%, and the lower limit is 58.0%; the grading upper limit of 4.75mm recycled coarse aggregate is 68.0%, and the lower limit is 38.0%; the grading upper limit of 4.75mm recycled fine aggregate is 68.0%, and the lower limit is 38.0%; the grading upper limit of 4.75mm recycled coarse ... The upper limit of aggregate grading is 32.0%, and the lower limit is 22.0%; the upper limit of grading of 2.36mm recycled fine aggregate is 28.0%, and the lower limit is 16.0%; the upper limit of grading of 0.60mm recycled fine aggregate is 15.0%, and the lower limit is 8.0%; the upper limit of grading of 0.075mm recycled fine aggregate is 3.0%, and the lower limit is 1.0%; at the same time, in order to avoid contact damage of aggregates due to the inter-particle inter-extrusion effect, the three specifications of recycled aggregates are mixed and the grading is adjusted so that the synthetic grading of recycled aggregate is close to the median grading required by the specification. The grading ratio of the 0-5mm recycled fine aggregate, the 5-10mm recycled coarse aggregate and the 10-25mm recycled coarse aggregate is 24:26:50; the grading curve is as follows Figure 3 As shown, Figure 3 In the process, the gradation curve is close to the middle value of the designed gradation and meets the above requirements, so as to avoid contact damage caused by the inter-particle squeeze effect and ensure the superior strength and stability of the material.

[0049] The mix ratio of the three is determined based on the optimal moisture content, maximum dry density, and 7d infinite lateral compressive strength of the fly ash stabilized recycled aggregate formed by mixing lime, fly ash and recycled aggregate to ensure that the optimal moisture content, maximum dry density, 7d infinite lateral compressive strength, mass loss rate and residual compressive strength ratio of the antifreeze performance test meet the corresponding design requirements: the optimal moisture content is 11.1%, the maximum dry density is 2.015g / cm 3 , 7d infinite lateral compressive strength is 2.80MPa; finally, the mass ratio of the lime, fly ash, and synthetic recycled graded aggregate is determined to be 8:17:75. The fly ash stabilized recycled aggregate prepared with this mix ratio meets the above requirements. Among them, the 7d infinite lateral compressive strength result is as follows Figure 4 As shown;

[0050] S2: Root design road structure layer:

[0051] According to the grade of conventional municipal roads of level 2 and below and the design situation of equivalent car traffic volume of less than 7,500 vehicles per day and night, the fly ash stabilized recycled aggregate mixed according to the recycled aggregate particle grading and material mix ratio determined in S1 is set as a multi-layer road structure layer paved from bottom to top; the multi-layer road structure layer includes an upper base layer, a lower base layer and a low base layer arranged in sequence from top to bottom, wherein the thickness of the upper base layer is 18 cm, the thickness of the lower base layer is 18 cm, and the thickness of the low base layer is 16 cm. The structural schematic diagram of the multi-layer road structure layer is as follows: Figure 5 As shown;

[0052] S3: Paving of fly ash stabilized recycled aggregate:

[0053] In view of the large variability of construction waste performance, indoor performance tests are carried out on lime, fly ash and synthetic recycled graded aggregate respectively. The performance tests include screening test, physical property test and chemical property test. After the results of each test meet the requirements of "Code for Construction and Quality Acceptance of Urban Road Engineering" (CJJ1-2019) and "Technical Specifications for Construction of Highway Pavement Base" (JTG / T F20-2015), the lime, fly ash and synthetic recycled graded aggregate that meet the test requirements are mixed according to the material mix ratio determined in S1 to form fly ash stabilized recycled aggregate. Then, indoor tests such as compaction test, ash dosage test, unconfined compressive strength test and antifreeze performance test and on-site performance tests such as core test, rebound deflection test and compaction degree test are carried out on the fly ash stabilized recycled aggregate. After the parameters of each test result meet the standards, it is ensured that each test result meets the corresponding design requirements: the optimal moisture content measured by the compaction test is not less than 11.1% and the maximum dry density is not less than 2.015g / cm3; in the ash dosage test, the upper base, lower base and The dosage range of base ash should meet 33%~34%; the 7d unconfined compressive strength should not be less than 2.8MPa; the mass loss rate of anti-freeze performance test should be lower than 5% and the residual compressive strength ratio should be greater than 70%; the core sampling test should meet the requirements that the core sample is smooth and straight, and the average thickness of the core samples of the base, lower base and upper base should meet the requirements of 155mm, 175mm and 175mm respectively, and the three parts of the 30d coring strength should meet the requirements of 7~9MPa; the representative value of 9d deflection in the rebound deflection test should be greater than 20 (0.01mm); the compaction degree test should be greater than 95%; at the same time, the fly ash stabilized recycled aggregate should meet the requirements of no obvious segregation of coarse and fine aggregates and consistent color of the mixture to ensure its stable performance.

[0054] Before the fly ash stabilized recycled aggregate is spread, a process is set up to transport the fly ash stabilized recycled aggregate to the construction site, and measures are taken to prevent moisture loss during transportation. The box should be tightly covered with tarpaulin and can only be opened when unloading before paving;

[0055] According to the paving structure of fly ash stabilized recycled aggregate designed in S2, the paving, rolling and curing construction procedures are carried out, that is, the construction process includes mixing, transportation, paving, rolling, curing and other steps. Among them, the paving construction of the base material is carried out by a paver, and the paving speed is controlled at 1.0-1.5m / min; after the paving is completed, the traffic is closed and watering is carried out for 7 days.

[0056] Performance Test:

[0057] In order to verify the feasibility of preparing fly ash stabilized recycled aggregate materials for actual road use, a 200-meter test section was conducted, all of which were carried out using the above steps and requirements:

[0058] (1) Compaction test

[0059] According to the "Testing Procedure for Stabilized Materials of Inorganic Binders for Highway Engineering" (JTG 3441-2024), the fly ash stabilized recycled aggregate material prepared by the mix ratio disclosed in the present invention was subjected to a compaction test, and the optimum moisture content of the fly ash stabilized recycled aggregate material was 11.1%, and the maximum dry density was 2.015 g / cm 3 , in line with design requirements;

[0060] (2) The ash dosage of the mixture used in the test section was tested by EDTA titration method. The test was carried out in accordance with the "Test Code for Stabilized Materials of Inorganic Binders for Highway Engineering" (JTG 3441-2024). Two groups of tests were set up. The test results are shown in Table 1. It can be seen from Table 1 that the ash dosage of the mixture meets the design requirements of 33% to 34% for the upper base, lower base and bottom base.

[0061] Table 1 Example parameters

[0062]

[0063] (3) Unconfined compressive strength test:

[0064] According to the "Test Code for Stabilized Materials with Inorganic Binders for Highway Engineering" (JTG 3441-2024), the unconfined compressive strength test was carried out. The fly ash stabilized recycled aggregate used in the test section was made into an unconfined compressive strength specimen of Φ150mm×150mm. The pressure testing machine was pressurized at a loading rate of 1mm / min, and the pressure was maintained for 2min for compaction. When immersed in water, it was immersed in 20±2℃ water. The test results are as follows: Figure 6 As shown, from Figure 6It can be seen that the material strength development of the three-part structure (upper base, lower base and lower base) is basically the same. The 7d unconfined compressive strength of the lower base has met the technical requirements of the extra-heavy and extremely heavy traffic of expressways in the technical specifications (not less than 1.1MPa), and the 7d unconfined compressive strength of the upper and lower bases are close to meeting the above technical requirements; the materials of the three-part structure all exceeded 7MPa at 28d, and the 28d strength was more than 5MPa higher than the 1d strength.

[0065] (4) Antifreeze performance test:

[0066] The antifreeze performance test was carried out in accordance with the "Test Procedure for Inorganic Binder Stabilized Materials for Highway Engineering" (JTG 3441-2024). The mixture used in the test section (flyash stabilized recycled aggregate material) was made into a standard specimen and subjected to 5 freeze-thaw cycles. Figure 7 is the mass loss rate and residual compressive strength ratio of the specimen after freezing and thawing, Figure 7 (a) It can be seen that the mass loss rate of all base specimens after freezing and thawing is less than 5%, and the average value is 2.0%. Figure 7 (b) It can be seen that the residual compressive strength ratio of the base specimens after freeze-thaw is greater than 70%, with an average value of 81.7%, and the anti-freeze performance is good; the mass loss rate meets the standard of less than 5%, and the residual compressive strength ratio meets the standard of greater than 70%.

[0067] (5) Coring inspection:

[0068] The test section was drilled and sampled twice, the first time was on the 7th day after paving, and the second time was on the 30th day after paving. Through on-site core drilling test, the subbase, lower base and upper base core samples were completely taken out twice, such as Figure 8 and 9 As shown, Figure 8 (a) and Fig. 9 (a) is a schematic diagram of on-site core drilling. Figure 8 (b) and Fig. 9 (b) are schematic diagrams of core samples taken from two core drillings. By observing the core samples, it is found that the aggregate gradation is good and the core samples are smooth and straight, which meets the standard requirements. This shows that the quality of the lime fly ash stabilized recycled aggregate base is good and can meet the actual use needs.

[0069] (6) Core sample thickness measurement

[0070] The core samples obtained above are numbered according to the pile number. The two core samples obtained at the same pile number have the same number. After two core samplings, the thickness of the bottom base, lower base, and upper base are measured respectively. The test results are as follows: Fig.10The average thickness of the base layer is 162.0mm, the average thickness of the lower base layer is 179.0mm, and the average thickness of the upper base layer is 179.6mm. All measured values ​​meet the requirements of the standard specification (the average thickness of the core sample base layer is greater than 155mm, the average thickness of the lower base layer is greater than 175mm, and the average thickness of the upper base layer is greater than 175mm). The test is qualified. After testing the core sample thickness, the unconfined compressive strength test is carried out. The results are as follows Fig.11 As shown in the figure, the subbase, lower base and upper base tested twice all meet the strength design requirements. The average value of the second test of the subbase is 3.52MPa higher than that of the first test, the lower base is 3.74MPa higher, and the upper base is 3.66MPa higher. The strength of the second coring (30d) remains in the range of 7 to 9MPa, which is consistent with the strength change law of general fly ash stabilized base materials.

[0071] (7) Rebound deflection test

[0072] According to the on-site test procedures and the T0953-2008 drop weight deflectometer test deflection method, the rebound deflection test was conducted on the roadbed before paving in the test section and the fly ash stabilized recycled aggregate base 9 days after paving. The results are shown in Table 2. The representative deflection value of the roadbed before paving was 219.53 (0.01mm), which was relatively large. The representative deflection value of the fly ash stabilized recycled aggregate base 9 days after paving was 24.89 (0.01mm), which was 88.67% lower than that before paving. The test of the fly ash stabilized recycled aggregate base met the standard of greater than 20 (0.01mm), indicating that the bearing capacity of the roadbed in the test section increased and the anti-deformation ability was improved.

[0073] Table 2 Rebound deflection test results

[0074]

[0075] (9) Compaction test:

[0076] According to the "Highway Roadbed and Pavement Field Test Specification" (JTG 3450-2019), the compaction test was carried out using the sand injection method. The test section was tested twice for compaction, and each structural layer was tested 5 times each time. The test results are as follows: Fig.12 As shown. Fig.12 It can be seen that the compaction degree of the test section base layer in the two tests was above 98%, both meeting the 95% test standard, indicating that the selected mix ratio and compaction process have good effects.

[0077] In summary, the fly ash stabilized recycled aggregate prepared by the particle size ratio and the proportion of each component provided by the method shows good unconfined compressive strength and frost resistance in actual use. The ash dosage of the mixture, the core sample strength after construction, and the compaction degree all meet the actual requirements, and the anti-deformation ability is improved. Under the premise of ensuring the technical performance of the material, the method greatly increases the dosage of recycled aggregate from construction waste, achieves 100% replacement of natural aggregate, greatly improves the utilization rate of construction waste, protects the ecological environment, and alleviates the shortage of natural materials. At the same time, the present invention proposes a new paving application method for municipal roads, which greatly improves the feasibility of practical application.

[0078] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for stabilizing recycled aggregate by using lime fly ash in a municipal road base, characterized in that: The following steps are involved: S1: Determine the particle size distribution and material mix ratio of recycled aggregate: The crushed construction waste recycled aggregate is screened into recycled coarse aggregate and recycled fine aggregate according to the particle size specifications, and the gradation ratio of the recycled coarse aggregate and the recycled fine aggregate is determined according to the crushing index, water absorption rate and gradation curve of the construction waste recycled aggregate to ensure that the crushing index, water absorption rate and gradation curve of the synthetic recycled graded aggregate formed by mixing the recycled coarse aggregate and the recycled fine aggregate meet the corresponding design requirements; Determine the mix ratio of the three based on the optimal moisture content, maximum dry density, and 7d unconfined compressive strength of the fly ash stabilized recycled aggregate formed by mixing lime, fly ash, and synthetic recycled graded aggregate, to ensure that the optimal moisture content, maximum dry density, 7d unconfined compressive strength, mass loss rate in the frost resistance test, and residual compressive strength ratio meet the corresponding design requirements; S2: Design road structure layer: According to the grade requirements and traffic volume requirements of municipal roads, the road structure layer paved with fly ash stabilized recycled aggregate mixed according to the recycled aggregate particle grading and material mix ratio determined in S1 is set as a multi-layer road structure layer paved from bottom to top; S3: Paving of fly ash stabilized recycled aggregate: Conduct screening tests, physical property tests, and chemical property tests on lime, fly ash, and synthetic recycled graded aggregates to ensure that each test result meets the corresponding standards; Carry out compaction test, ash dosage test, 7d unconfined compressive strength test, frost resistance test indoor test, core drilling test, rebound deflection test, compaction test on-site performance test for fly ash stabilized recycled aggregate to ensure that each test result meets the corresponding design requirements; The paving, rolling and curing construction procedures are carried out according to the paving structure of fly ash stabilized recycled aggregate designed in S2.

2. A method for stabilizing recycled aggregate by using lime fly ash in a municipal road base according to claim 1, characterized in that: In S1, the mass ratio of the lime, fly ash and synthetic recycled graded aggregate is 8:17:

75.

3. The method of using lime fly ash to stabilize recycled aggregate in a municipal road base according to claim 1, characterized in that: In S1, the recycled coarse aggregate includes two particle sizes of 5-10 mm and 10-25 mm; the recycled fine aggregate includes one particle size of 0-5 mm; The grading ratio of the 0-5 mm recycled fine aggregate, the 5-10 mm recycled coarse aggregate and the 10-25 mm recycled coarse aggregate is 24:26:

50.

4. The method of using lime fly ash to stabilize recycled aggregate in a municipal road base according to claim 1, characterized in that: In S2, the multi-layer road structure layer includes an upper base layer, a lower base layer and a low base layer arranged in sequence from top to bottom, wherein the thickness of the upper base layer is 18 cm, the thickness of the lower base layer is 18 cm, and the thickness of the bottom base layer is 16 cm.

5. The method of using lime fly ash to stabilize recycled aggregate in a municipal road base according to claim 1, characterized in that: In S1, the crushing index of recycled aggregates from construction waste is that the crushing rate of recycled coarse aggregate is less than 22%, and the crushing rate of recycled fine aggregate is less than 30%; The water absorption rate of recycled aggregate from construction waste is less than 9.5%; The specification requirements for the gradation curve of mixed recycled aggregates from construction waste are: the upper limit of the gradation curve of 19.0mm recycled coarse aggregate is 86.0%, and the lower limit is 68.0%; the upper limit of the gradation curve of 9.5mm recycled coarse aggregate is 58.0%, and the lower limit is 38.0%; the upper limit of the gradation curve of 4.75mm recycled fine aggregate is 32.0%, and the lower limit is 22.0%; the upper limit of the gradation curve of 2.36mm recycled fine aggregate is 28.0%, and the lower limit is 16.0%; the upper limit of the gradation curve of 0.60mm recycled fine aggregate is 15.0%, and the lower limit is 8.0%; the upper limit of the gradation curve of 0.075mm recycled fine aggregate is 3.0%, and the lower limit is 1.0%.

6. The method of using lime fly ash to stabilize recycled aggregate in a municipal road base according to claim 1, characterized in that: In S2, the grade of municipal roads is level 2 and below, and the traffic volume requirement is equivalent to less than 7,500 cars per day and night.

7. The method of using lime fly ash to stabilize recycled aggregate in a municipal road base according to claim 1, characterized in that: In S1, the optimum moisture content is 11.1% and the maximum dry density is 2.015 g / cm 3 ; The 7d unconfined compressive strength is 2.80MPa.

8. The method of using lime fly ash to stabilize recycled aggregate in a municipal road base according to claim 1, characterized in that: In S3, the test results of screening test, physical property test and chemical property test of lime, fly ash and recycled aggregate shall meet the requirements of CJJ1-2019 Code for Construction and Quality Acceptance of Urban Road Engineering and JTG / T F20-2015 Technical Specifications for Construction of Highway Pavement Base; The test results of the compaction test, ash dosage test, 7d unconfined compressive strength test, frost resistance test, and the core drilling test, rebound deflection test, and compaction test of the indoor test of fly ash stabilized recycled aggregate must meet the following standards: the optimum moisture content of the compaction test is not less than 11.1% and the maximum dry density is not less than 2.015g / cm 3 ; In the ash dosage test, the ash dosage range of the upper base, lower base and bottom base is 33%~34%; the 7d unconfined compressive strength is not less than 2.8MPa; the mass loss rate of the antifreeze performance test is lower than 5%, and the residual compressive strength ratio is greater than 70%; the core samples of the core drilling test are smooth and straight, the average thickness of the bottom base of the core sample is greater than 155mm, the average thickness of the lower base is greater than 175mm and the average thickness of the upper base is greater than 175mm, and the 30d coring strength meets the requirements of 7~9MPa; the representative value of 9d deflection in the rebound deflection test is greater than 20 (0.01mm); the compaction degree test meets the requirements of greater than 95%.

9. The method of using lime fly ash to stabilize recycled aggregate in a municipal road base according to claim 1, characterized in that: In S3, the paving method is: paving by a paver with a paving speed of 1.0 to 1.5 m / min.

10. The method of using lime fly ash to stabilize recycled aggregate in a municipal road base according to claim 1, characterized in that: Before the fly ash stabilized recycled aggregate is spread, a process of transporting the fly ash stabilized recycled aggregate to the construction site is set up, and measures are taken to prevent moisture loss during transportation.